Carbon monoxide in foundry air. - Virtamo, Matti; Tossavainen, Antti (Scandinavian Journal of Work, Environment & Health, 1976)
The concentration of carbon monoxide in the air of 67 iron, steel, or copper alloy foundries using sand molding was measured. About 1,100 carbon monoxide determinations were made. High concentrations of carbon monoxide were found in the area around the cupolas and the casting sites in iron foundries. The blood carboxyhemoglobin levels of 145 workers from iron foundries were measured. The carboxyhemoglobin level of 6% was exceeded in 26% of the nonsmokers and in 71% of the smokers.
Keywords: carbon monoxide; carboxyhemoglobin level; foundry air; foundry work